Reporting Clientele Contacts in Workload - Diane D. Craig; Glenn D. Israel (EDIS, 2016)
Each fall UF/IFAS faculty are asked to report on their Extension activities and accomplishments over the past year, including the contact made with Extension clientele through both direct and indirect methods. This 5-page fact sheet describes how to report these interactions in Workload. Written by Diane Craig and Glenn D. Israel, and published by the Department of Agricultural Education and Communication, October 2016.